2011
DOI: 10.1590/s1806-00132011000300004
|View full text |Cite
|
Sign up to set email alerts
|

Atividade laboral em pacientes atendidos em um serviço ambulatorial de dor crônica

Abstract: Rev Dor. São Paulo, 2011 jul-set;12(

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
3
3
0
Order By: Relevance
“…The author found that among the 3,182 individuals in the study, prevalence of chronic pain was higher among females (56.81%). This is similar to data found in a study conducted in the Netherlands, which showed the predominance of chronic pain in women (53.9%), and to a study involving the population of the city of Salvador, where 55.4% of individuals presenting with chronic pain were females (18).…”
Section: Discussionsupporting
confidence: 90%
“…The author found that among the 3,182 individuals in the study, prevalence of chronic pain was higher among females (56.81%). This is similar to data found in a study conducted in the Netherlands, which showed the predominance of chronic pain in women (53.9%), and to a study involving the population of the city of Salvador, where 55.4% of individuals presenting with chronic pain were females (18).…”
Section: Discussionsupporting
confidence: 90%
“…Mean age for both groups was the fourth decade of life. This result is very similar to that found in a study at the same pain service from 2006 to 2010, with active patients and inactive patients on medical leave, where mean was 46 and 45 years, respectively 9 . This age group is in productive age and chronic pain interference with occupational life of these patients generates severe economic problems, such as high medical leave and disability retirement rates.…”
Section: Discussionsupporting
confidence: 90%
“…Our study, similar to other authors 9 , could not establish that pain intensity was reason for withdrawing from work. Severe pain was observed in similar percentages for both active and inactive groups.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…It is important to stress that chronic neuropathic pain management should be individualized, multimode and based on parameters such as current disease history, preexisting diseases, physical evaluations, lab exams, complementary exams, cost of drugs as well as their side effects, contraindica-tions and follow up of responses to previously used methods 5 . Given the rich symptomatology of the case and neuropathic pain pathophysiology complexity, physicians should not give up when facing management with modest results, but rather should persist in the search for pain relief to provide better quality of life to patients 6 . Patient's poor performance with planned strategies and the complexity of chronic neuropathic pain healing process may lead physicians, after some fruitless attempts, to a feeling of dismay.…”
Section: Discussionmentioning
confidence: 99%